ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN SISTEM INFORMASI MANAJEMEN DI PUSKESMAS SIBANDE TAHUN 2022 - Aulia, Aulia (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2024)
Implementation of the puskesmas information system referred to in Permenkes No. 31 of 2014, each puskesmas is required to organize a puskesmas information system, both district/city, which can be held electronically or non-electronically. And in the implementation of the Health Center Information System, cleaning, validation, and grouping of needs must be carried out. The regulation of the puskesmas information system aims to realize the implementation of an integrated puskesmas information system, ensure the availability of quality, sustainable and easily accessible data and information, improve the quality of health development in its working area through strengthening puskesmas management. Factors related to the quality of the management information system at the Puskesmas are individual factors, organizational factors and psychological factors. Individual factors consist of abilities and expertise, individual background and demographics. Organizational factors consist of human resources, leadership, compensation (financial and non-financial), structure and job design. While psychological factors consist of perception, attitude, personality, learning and motivation. (Gibson, 2009). This type of research is quantitative research with multiple regression. Quantitative research. The sample in this study were all Health Officers at the Sibande Health Center as many as 45 people. From the chi-square test based on the Ability variable, the value of p = 0.015 <0.05 was obtained, the HR variable was obtained by the value of p = 0.004 <0.05, Compensation was obtained by the value of p = 0.002 <0.05, Attitude was obtained by the value of p = 0.000 < 0.05, it can be concluded that the variables Capability, HR, Compensation, and Attitude are related to the Implementation of the Sibande Health Center Information System in 2022.